Pelatihan perencanaan pembangunan bagi aparatur desa di Desa Baumata Utara Kecamatan Taebenu Kabupaten Kupang - Nursalam Nursalam (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Abstract The village development planning is a routine activity carried out in order to carry out development. Activities that involve many parties (stakeholders) include all members of the community and village apparatus. One of the demands is that it requires planning skills from village apparatus, their capacity is needed in order to anticipate and interpret various development programs according to the demands and needs of the community by utilizing the potential and resources available in the village. The fact indicate that the planning capacity of the apparatus is still not optimal, the indication is that the Proposed list of village development activity plans (DURK-Desa) does not reflect the potential and needs of the village. Planning training for village apparatus aims to provide planning insights so that in the end they can carry out planning functions effectively. The method used in development planning training for village apparatus is the education method, in which village apparatus are given training to be able to apply village development planning analysis techniques with courses; (1) analysis of village potential; (2) SWOT analysis and; (3) formulation of alternative proposals for village development planning. To determine the success of the training, a success evaluation method was made, namely the method; (1) program evaluation; (2) evaluation of results and; (3) final evaluation of activities. The based on the evaluation of planning training, village apparatus have been able to carry out various activities, including; carry out a simple analysis of the potential for village development; SWOT analysis on village development planning and; able to formulate various alternative proposals for village development programs / projects based on the potential and problems faced by the community. Keywords: Development planning, competence, capacity